Dermal eosinophilic infiltrate in junctional epidermolysis bullosa. (4th June 2015) - Saraiya, Ami; Yang, Catherine S.; Kim, Jinah; Bercovitch, Lionel; Robinson‐Bostom, Leslie; Telang, Gladys
<x xml:space="preserve">Abstract</x> Junctional epidermolysis bullosa (JEB) is a rare genodermatosis characterized by a split in the lamina lucida usually because of mutations in LAMA3, LAMB3 and LAMC2 resulting in absence or reduction of laminin‐332. Rare subtypes of JEB have mutations in COL17A1, ITGB4, ITGA6 and ITGA3 leading to reduction or dysfunction of collagen XVII, integrin α6β4 and integrin α3. The classic finding under light microscopy is a paucicellular, subepidermal split. We describe the unusual presence of an eosinophilic infiltrate in the bullae and subjacent dermis in a neonate with JEB, generalized intermediate (formerly known as non‐Herlitz‐type JEB), discuss the histologic differential diagnosis for a subepidermal blister in a neonate, review the literature regarding cases of epidermolysis bullosa (EB) presenting with inflammatory infiltrates, and discuss mechanisms to explain these findings. This case highlights that eosinophils can rarely be seen in EB and should not mislead the dermatopathologist into diagnosing an autoimmune blistering disorder.